DRIVER COMPETENCY DETECTION AND ALERT SYSTEM USING IMAGE PROCESSING TECHNOLOGY FOR ROAD SAFETY - nongnuch, krommavut; Leelawongsarote, Saowalak; ปุบผาโสมตระกูล พงศ์กรณ์; ซาเฮาะ อนุชา; ขุนอาสา ตะวัน (Thai Interdisciplinary and Sustainability Review, 2025)
This article presents the development of a driver competency detection and alert system using image processing technology, aiming to enhance road safety and mitigate risks associated with driver impairment. The system assesses driving ability based on factors such as drowsiness, microsleep, yawning, and distraction, employing the Haar Cascades Algorithm for face and eye detection, key components in evaluating driver status. Upon detection of risky behaviors, an auditory alert is triggered to stimulate driver alertness and focus on driving. Experimental results demonstrate a face detection accuracy of 73.75% and an alert interpretation accuracy of 81.88%. Factors influencing performance include camera clarity, lighting conditions, and facial obstructions. The development of this system has the potential to reduce accidents, alleviate economic burdens from property damage and injuries, and promote road safety, aligning with sustainable development goals in transportation safety.